ON HELICES AND SLANT HELICES IN THE LIGHTLIKE CONE - Kulahci, Mihriban Alyamac; Almaz, Fatma; Bektas, Mehmet (Honam Mathematical Soc, 2018)
In this paper, we investigate the notions of helix and slant helices in the lightlike cone. Using the asymptotic orthonormal frame we present some characterizations of helices and slant helices.
Keywords: Asymptotic orthonormal frame; spacelike curve; helix